2003
DOI: 10.1111/j.1651-2227.2003.tb02583.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying children at risk for language impairment: screening of communication at 18 months

Abstract: Aim: To investigate the possibility of identifying children at risk for language impairment based on a new screening instrument to assess communication and language skills at 18 mo of age. Methods: At 18 mo, 58 children were assessed with a screening instrument for communication and language consisting of a professional assessment and a parents' questionnaire. Students of speech and language pathology, well trained in child language assessment, carried out the professional assessment, which was based on observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 23 publications
0
14
0
3
Order By: Relevance
“…A temporal link between language and symbolic play development has been proposed (Snyder, 1987). Early levels of symbolic play have also been suggested to predict later language development in toddlers with LI (Bruce, Kornfält, Radeborg, Hansson, & Nettelbladt, 2003) as well as in populations of children with other forms of special needs (O'Toole & Chiat, 2006). Playbehaviours have been found to support symbolization capacity by providing the child with a space to explore the sense of self and others (Winnicott, 1971), as well as a bridge between the inner world and the reality (Vygotskij, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…A temporal link between language and symbolic play development has been proposed (Snyder, 1987). Early levels of symbolic play have also been suggested to predict later language development in toddlers with LI (Bruce, Kornfält, Radeborg, Hansson, & Nettelbladt, 2003) as well as in populations of children with other forms of special needs (O'Toole & Chiat, 2006). Playbehaviours have been found to support symbolization capacity by providing the child with a space to explore the sense of self and others (Winnicott, 1971), as well as a bridge between the inner world and the reality (Vygotskij, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…to avoid over-prediction) of the screening. For example, in the study by Bruce et al [39] some children, all boys, who had been identified as belonging to a risk group at 18 months of age, but at the follow up did not evidence language problems (i.e. false positives).…”
Section: Ear L Y Scr E En Ing Of Co Mm Uni Ca Ti O N Skillsmentioning
confidence: 93%
“…language impairment and neuropsychiatric problems. Early communicative problems can also reflect a risk for language impairment [39] or neuropsychiatric problems [37,44]. Language comprehension and play behaviour manifested in symbolic play, have been shown to be of particular importance in predicting language problems manifested three years later.…”
Section: Ear L Y Scr E En Ing Of Co Mm Uni Ca Ti O N Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, no reliable and accurate means exists that would enable early identification of children who will later have clinically significant language impairment. For example, with regard to outcomes for late talkers, various potential predictors, such as level of expressive delay, receptive language, social engagement and joint attention, as well as gestures and symbolic play (e.g., Bates & Dick, 2002;Bruce, Kornfält, Radeborg, Hansson, & Nettelbladt, 2003;Dale et al, 2003;Rescorla & Goossens, 1992;Rescorla & Merrin, 1998), have been tested, but none of these have proven to have consistent predictive value. However, there are indications that the severity and multitude of early delays may serve as a guide (Ellis & Thal, 2008;Paul & Roth, 2011;Rescorla, 2009).…”
mentioning
confidence: 99%